360° Feedback: Ready, Fire, Aim—Issues With Improper Implementation. Issue 1 (January 2014) - Vukotich, George
Abstract This article looks at 360° feedback, as well as mistakes and misuses that are often made in its implementation and use. Too often individuals look for tools to give them facts to support predetermined opinions rather than gathering facts to support individuals in their growth and development process. By identifying these issues and addressing them up front, larger issues that can negatively affect the overall culture of an organization can be avoided.